The State and Critical Assessment of the Sharing Economy in Europe - Vida Česnuitytė; Bori Simonovits; Andrzej Klimczuk; Bálint Balázs; Cristina Miguel; Gabriela Avram (The Sharing Economy in Europe: Developments, Practices, and Contradictions, 2022)
The chapter is the final one in the volume of collected papers aiming to discuss the sharing economy in Europe. The idea of the book emerged within the research network created by the COST Action CA16121 'From Sharing to Caring: Examining Socio-Technical Aspects of the Collaborative Economy.' The authors of the chapter sum up theoretical and empirical materials as well as country-specific cases provided in the book. The article critically assesses the current status of the sharing economy in European countries by highlighting major controversial issues related to deregulation, market disruption, or social inequality. The authors conclude that, considering the comprehensive and up-to-date materials collected and analysed in the book, it may become an outstanding source of knowledge and a practical tool in the process of expansion of the sharing economy in Europe and beyond.
Keywords: D16; L86; Z18; Z13; 330; Sharing Economy; Critical Assessment of the Sharing Economy; Controversies of the Sharing Economy